2019
DOI: 10.1097/mpa.0000000000001205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Intraductal Papillary Mucinous Neoplasms in Healthy and Ill Populations Detected by Ultrasonography

Abstract: Objectives:The aim of this study was to establish the prevalence of intraductal papillary mucinous neoplasms (IPMNs) without and with highrisk stigmata (HRS)/worrisome features (WF) and the epidemiologic association between IPMNs and other diseases.Methods: Ultrasound examinations of outpatients were evaluated. The IPMN was confirmed by magnetic resonance imaging. The prevalence of IPMNs and HRS/WF IPMNs was calculated. The association between IPMNs and other diseases was studied. Results:The prevalence rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
6
2
Order By: Relevance
“…10 In these 2 studies, the risk factor associated with IPMNs was age, which was consistent with the findings of our study. In addition, in a study by Ricci et al, 12 the female sex was positively associated with the presence of IPMNs (OR, 1.9; P < 0.001), which was not examined in our study. We identified other factors associated with IPMN.…”
Section: Discussioncontrasting
confidence: 69%
“…10 In these 2 studies, the risk factor associated with IPMNs was age, which was consistent with the findings of our study. In addition, in a study by Ricci et al, 12 the female sex was positively associated with the presence of IPMNs (OR, 1.9; P < 0.001), which was not examined in our study. We identified other factors associated with IPMN.…”
Section: Discussioncontrasting
confidence: 69%
“…(women: OR 1.9, p<0.001) were predictors of pancreatic cysts in a study of outpatients who underwent AUS(21). Although not significant, PCLs also tended to be more common in women than men in the present study as well (OR 1.55, 95% CI 0.94-2.56).…”
contrasting
confidence: 53%
“…Furthermore, Soroida et al reported that gender (women: OR 1.29, p=0.001) as well as age were predictors of PCLs in a study of AUS examinees at medical checkups ( 20 ). Ricci et al also showed that age and gender (women: OR 1.9, p<0.001) were predictors of pancreatic cysts in a study of outpatients who underwent AUS ( 21 ). Although not significant, PCLs also tended to be more common in women than men in the present study as well (OR 1.55, 95% CI 0.94-2.56).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…IPMNs are grossly visible (typically > 5 mm) intraductal epithelial neoplasms of mucin-producing cells, first recognized by the World Health Organization (WHO) in 1996 [5]. IPMNs, that arise in the main pancreatic duct and/or their branches, are common lesions, with an estimated prevalence of 3-6% in the general population and more than 10% in older adults [6][7][8]. These tumors represent the most common pancreatic cystic neoplasms undergoing resection [9,10].…”
Section: Introductionmentioning
confidence: 99%